Evaluasi Produktivitas Kayu dalam Pengelolaan Hutan Rakyat Lestari Skema Forest Stewardship Council di Jawa Timur - Hermudananto; Nunuk Supriyatno (Fakultas Kehutanan Universitas Jambi, 2019)
Certified sustainable community forests in Indonesia continue to grow in number for the Forest Stewardship Council (FSC) scheme. At least three aspects have been fulfilled namely, sustainable production, protected ecosystems, and social contribution. However, the problem of 'need cutting' in community forests has the potential to hamper forest management in terms of timber harvesting. Three FSC certified community forest management units in East Java, Enggal Mulyo, KSU KAM KTI, KSU Bromo Mandiri KTI, demonstrated this challenge through evaluating the log harvest records, discussions with managers and farmers, and field observations. Harvesting plans are only based on periodic tree inventory data that does not take into account the farmers' harvest needs, such as weddings or celebrations. Therefore, all annual timber production targets cannot be achieved, indicating that need harvesting and delayed logging are also still visible in internationally certified sustainable forest management. Support from managers and parties is still needed so that the management plan can be implemented properly. The owner of the FSC scheme also needs to evaluate their standard requirements for implementing timber harvesting on a more realistic scale of community forests.